Investigation of Heat Sink Efficiency for Electronic Component Cooling Applications - Staliulionis, Z.; Zhang, Z.; Pittini, R.; Andersen, M. A. E.; Tarvydas, P.; Noreika, A. (Elektronika ir Elektrotechnika, 2014)
Research and optimisation of cooling of electronic components using heat sinks becomes increasingly important in modern industry. Numerical methods with experimental real-world verification are the main tools to evaluate efficiency of heat sinks or heat sink systems. Here the investigation of relatively simple heat sink application is performed using modelling based on finite element method, and also the potential of such analysis was demonstrated by real-world measurements and comparing obtained results. Thermal modelling was accomplished using finite element analysis software COMSOL and thermo-imaging camera was used to measure the thermal field distribution. Ideas for future research involving improvement of the experimental setup and modelling verification are given. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6167